Investigation of Serum and Macular Carotenoids in Central Serous Chorioretinopathy - Ji, Yuying; Gan, Yuhong; Su, Yongyue; Zhang, Yining; Li, Miaoling; Mi, Lan; Zuo, Chengguo; Wen, Feng (Frontiers in Medicine, 2022)
Purpose This study aimed to evaluate serum lutein and zeaxanthin levels and macular pigment optical density (MPOD) in central serous chorioretinopathy (CSC). Methods Fifty-four patients with acute CSC (28–56 years old; 44 men and 10 women) and 62 matched controls were enrolled. Serum lutein and zeaxanthin were measured using the high-performance liquid chromatography–tandem mass spectrometry (HPLC–MS/MS) method. MPOD was measured at 7° of eccentricity and reported in parameters as “max” and “mean” optical density (OD) (Visucam 200; Carl Zeiss Meditec). MPOD was re-measured in 9 patients whose subretinal fluid was absorbed. Results The average max OD and the mean OD in CSC were 0.275 ± 0.047 d.u. and 0.098 ± 0.018 d.u., respectively, which were significantly lower than the control (p < 0.001). The average MPOD value in the unaffected eyes of patients with CSC was 0.298 ± 0.045 for max OD, 0.106 ± 0.017 for mean OD, and both were significantly lower compared with the affected eyes (p < 0.001 for max OD, p = 0.01 for mean OD). In the 9 follow-up patients, the decrease in MPOD was partially recovered. The mean serum level was 409.80 ± 182.52 ng/ml for lutein and 22.97 ± 12.23 ng/ml for zeaxanthin in patients with CSC. In controls, the mean serum level was 393.38 ± 202.44 ng/ml for lutein and 22.16 ± 10.12 ng/ml for zeaxanthin. The difference was not statistically significant (p = 0.649, p = 0.698, respectively). Conclusion MPOD decreased within 7° of eccentricity in CSC without serum lutein and zeaxanthin changes. The decrease may be due to the subretinal fluid. Whether local oxidative stress is involved in CSC and the supplementation with lutein and zeaxanthin is helpful for CSC requires further investigation.